Entrepreneurship-Based Education Innovation Model: Alternative Strategies for Building a Participatory Learning Ecosystem - Jalal, Jalal; Asykur, Muamar; Alfian, Andi (International Conference On Association Of Indonesian Entrepreneurship Study Programs, 2024)
This research aims to explore the concept  of educational entrepreneurship as a transformational approach in designing an education system that is more adaptive to the challenges of the 21st century. This approach was born out of the need to overcome the limitations of the conventional education system which is often bureaucratic, rigid, and less responsive to social, economic, and technological dynamics. Using descriptive qualitative methods based on literature studies and case studies, this study analyzes various models of educational innovation built by education entrepreneurs in Indonesia, such as digital platforms, community-based schools, and nature-based learning. The results of the study show that educational entrepreneurs play an important role as agents of change who are able to create an alternative education ecosystem that is participatory, contextual, and solution-based. The models developed have proven to be effective in improving access, curriculum flexibility, and community participation in the educational process. In addition, they are able to combine social values, technological innovation, and economic sustainability in one integrative framework. In conclusion, educational entrepreneurship is a promising strategy to improve the inequality and stagnation of the formal education system. Therefore, this approach needs to receive structural support through policies, multi-sector partnerships, and strengthening the leadership capacity of entrepreneurship-based education